High‐resolution macromolecular crystallography at the FemtoMAX beamline with time‐over‐threshold photon detection. (8th December 2020) - Jensen, Maja; Ahlberg Gagnér, Viktor; Cabello Sánchez, Juan; Bengtsson, Åsa U. J.; Ekström, J. Carl; Björg Úlfarsdóttir, Tinna; Garcia-Bonete, Maria-Jose; Jurgilaitis, Andrius; Kroon, David; Pham, Van-Thai; Checcia, Stefano; Coudert-Alteirac, Hélène; et al.
Abstract : A 1.5 Å resolution crystal structure of bovine trypsin at room temperature has been determined using 150 fs X‐ray diffraction snapshots at the FemtoMAX beamline of the MAX IV facility. Abstract : Protein dynamics contribute to protein function on different time scales. Ultrafast X‐ray diffraction snapshots can visualize the location and amplitude of atom displacements after perturbation. Since amplitudes of ultrafast motions are small, high‐quality X‐ray diffraction data is necessary for detection. Diffraction from bovine trypsin crystals using single femtosecond X‐ray pulses was recorded at FemtoMAX, which is a versatile beamline of the MAX IV synchrotron. The time‐over‐threshold detection made it possible that single photons are distinguishable even under short‐pulse low‐repetition‐rate conditions. The diffraction data quality from FemtoMAX beamline enables atomic resolution investigation of protein structures. This evaluation is based on the shape of the Wilson plot, cumulative intensity distribution compared with theoretical distribution, I /σ, R merge / R meas and CC1/2 statistics versus resolution. The FemtoMAX beamline provides an interesting alternative to X‐ray free‐electron lasers when studying reversible processes in protein crystals.